Effect of root canal geometry and needle type on apical extrusion of irrigant: an ex vivo study - Büşra Serçe Fikirli; Bülent Altunkaynak; Güven Kayaoğlu (Acta Odontologica Turcica, 2022)
Objective: The aim was to evaluate the effect of root canal geometry on the amount of apical extrusion of irrigant, by testing different tapers and needle types. Materials and Method: Forty-three extracted single-rooted human mandibular premolar teeth were accessed. Experimental groups were instrumented to produce increasing amounts of taper in each successive group: Group 1 (#25/.02), Group 2 (#25/.04), Group 3 (#25/.06), and Group 4 (#25/.08) (n=43, each). Irrigation was done sequentially by using a 30-G open-ended flat needle, 30-G close-ended side-vented needle, and 27-G open-ended beveled needle. Flat and side-vented needles were each placed 3 mm short of the apex, while the beveled needle was placed as far as possible in the canal without binding. Extruded irrigant was collected in preweighed foam cubes. Statistical significance was set at p<0.05. Results: An increase in canal taper led to a decrease in the amount of extruded irrigant for the flat needle (p<0.05; Groups 1 and 2 versus 3 and 4) and side-vented needle (p<0.05; Groups 1 and 2 versus 4), but no significant effect was found for the beveled needle. The amount of extruded irrigant was greater with the flat than with the side-vented needle at all tapers and with the beveled needle at most tapers (p<0.05). The side-vented needle was generally associated with the least amount of extrusion. Conclusion: Given a constant needle insertion depth, the amount of apically extruded irrigant decreased as canal taper increased. The greatest and least amounts of extrusion were generally observed with the flat and side-vented needle, respectively.